Genocide and resistance Nr. 22(2) - Pušinskytė, Lijana; Rukšėnas, Alfredas; Okuličiūtė, Lina; Burinskaitė, Kristina; Marcinkevičienė, Dalia; Grikšaitė, Inesa; Vareikis, Vygantas; Anušauskas, Arvydas (Genocidas ir rezistencija, 2007)
Full Issue